Joyful Learning : An Effective Strategies for Interactive Drum Learning - Sembiring, Piter; Sukmayadi, Yudi; Gunara, Sandie (Jurnal Paedagogy, 2025)
This study aims to describe the application of the Joyful Learning method in drum lessons at Favore Music and to identify effective strategies in increasing student motivation and engagement. Using a qualitative descriptive approach with a participatory method, this study involved four drum students at Favore Music, Bandung City, through observation, structured interviews, and documentation. The data were analyzed through processes of data reduction, data display, and conclusion drawing, while method triangulation was applied to ensure research validity. The results showed that the application of Joyful Learning through rhythmic exploration, improvisation, and dynamic interaction was able to significantly increase student engagement. Learning strategies such as the use of backing tracks, variations in sticking exercises with various objects, and the challenge of tempo changes and fill-ins create a more interactive and enjoyable learning experience. This approach not only deepens students’ musical understanding but also increases their confidence and consistency in practicing. This study contributes to innovation in private music education and provides new insights into the effectiveness of experiential learning in improving the quality of drum learning.